LogicCrowd: Crowd-Powered Logic Programming Based Mobile Applications. (17th March 2017) - Phuttharak, Jurairat; Loke, Seng W
Abstract: Crowdsourcing has become an important problem-solving technique, for both traditional and mobile applications. There have been work on crowdsourcing particular database operations to humans, and work on spatial crowdsourcing or mobile crowdsourcing, where the workers are mobile device users. This paper presents LogicCrowd which extends logic programming, commonly used for knowledge-based applications, with crowdsourcing capabilities by adding operators to connect to crowdsourcing platforms, thereby enabling crowdsourcing via logic programs and crowd-powered knowledge-based applications. In LogicCrowd, we also introduce a novel unification approach called crowd unification that automatically leverages human knowledge for comparisons through the crowdsourcing paradigm. In addition, LogicCrowd is built on a Prolog platform running on Android mobile devices, thereby enabling logic-based spatial and mobile crowdsourcing. Our proposed method for combining rule-based reasoning and crowdsourcing via LogicCrowd programs is demonstrated in a range of scenarios. Because energy is an important consideration for mobile platforms, we also investigate the energy characteristics of the crowdsourcing operators in our LogicCrowd prototype. Our experiments show the relationships between crowdsourcing operations and energy consumption, and illustrate the factors influencing energy consumption when using crowdsourcing.